Про випереджаючу роль розвитку фізичного типу людини в процесі становлення палеолітичного виробництва - Гладилін, В.М. (Інститут археології НАН України, 2008)
Primarily progress of brain, and then, on the base of this process and due to it, with greater or lesser arrears, rise and further saltatory elaboration of tools and labor activity – such are the main two chronologically consequent components of progressive process of rise of Palaeolithic production.